Diversity of Filamentous Fungi Associated with Dairy Processing Environments and Spoiled Products in Brazil - Luana Virgínia Souza; Rafaela da Silva Rodrigues; Andressa Fusieger; Raiane Rodrigues da Silva; Sidney Rodrigues de Jesus Silva; Evandro Martins; Solimar Gonçalves Machado; Cinzia Caggia; Cinzia Lucia Randazzo; Antonio Fernandes de Carvalho (Foods, 2022)
Few studies have investigated the diversity of spoilage fungi from the dairy production chain in Brazil, despite their importance as spoilage microorganisms. In the present study, 109 filamentous fungi were isolated from various spoiled dairy products and dairy production environments. The isolates were identified through sequencing of the internal transcribed spacer (ITS) region. In spoiled products, Penicillium and Cladosporium were the most frequent genera of filamentous fungi and were also present in the dairy environment, indicating that they may represent a primary source of contamination. For dairy production environments, the most frequent genera were Cladosporium, Penicillium, Aspergillus, and Nigrospora. Four species (Hypoxylon griseobrunneum, Rhinocladiella similis, Coniochaeta rosae, and Paecilomyces maximus) were identified for the first time in dairy products or in dairy production environment. Phytopathogenic genera were also detected, such as Montagnula, Clonostachys, and Riopa. One species isolated from the dairy production environment is classified as the pathogenic fungi, R. similis. Regarding the phylogeny, 14 different families were observed and most of the fungi belong to the Ascomycota phylum. The understanding of fungal biodiversity in dairy products and environment can support the development of conservation strategies to control food spoilage. This includes the suitable use of preservatives in dairy products, as well as the application of specific cleaning and sanitizing protocols designed for a specific group of target microorganisms.